2010
DOI: 10.1523/jneurosci.5895-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Belief Inference during Cooperative Games

Abstract: Humans have the arguably unique ability to understand the mental representations of others. For success in both competitive and cooperative interactions, however, this ability must be extended to include representations of others' belief about our intentions, their model about our belief about their intentions, and so on. We developed a "stag hunt" game in which human subjects interacted with a computerized agent using different degrees of sophistication (recursive inferences) and applied an ecologically valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
178
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(191 citation statements)
references
References 43 publications
10
178
0
Order By: Relevance
“…This finding is in accordance with the behavioral results: participants adjusted their choices to the choices of their counterpart, making choices that were likely to yield a relatively higher payoff compared with the other. Recent neuroimaging studies have suggested that the mPFC and other regions of the mentalizing network compute prediction errors of the expected behavior of others (24,25), the uncertainty about other's strategy (38), and the level of strategic reasoning in competitive games (39). Thus, we suggest that mPFC activity at choice in our experiment is related to the strategic and competitive component of the social context and not simply to the presence of the other player.…”
Section: Discussionmentioning
confidence: 49%
“…This finding is in accordance with the behavioral results: participants adjusted their choices to the choices of their counterpart, making choices that were likely to yield a relatively higher payoff compared with the other. Recent neuroimaging studies have suggested that the mPFC and other regions of the mentalizing network compute prediction errors of the expected behavior of others (24,25), the uncertainty about other's strategy (38), and the level of strategic reasoning in competitive games (39). Thus, we suggest that mPFC activity at choice in our experiment is related to the strategic and competitive component of the social context and not simply to the presence of the other player.…”
Section: Discussionmentioning
confidence: 49%
“…However, previous work has shown that AVP administration increased cooperation following a cooperative gesture by one's partner in a repeated prisoner's dilemma (37), where cooperation might be mutually beneficial (38)-in line with the interdependent hypothesis (5). We believe that further investigation of AVP's role in social behavior would benefit from using computational theories that distinguish the different mechanism through which AVP may foster cooperative behavior in repeated interactions (35), particularly belief inference (33,36,39) and inferential limits in disorder (40).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a series of neuroimaging studies of social interactions have used depth of social reasoning (theory of mind) to describe individual differences in strategic behavior (Hampton et al, 2008;Coricelli and Nagel, 2009;Yoshida et al, 2010). In contrast to our study, these experiments have revealed an important role for the dorsal medial prefrontal cortex in social reasoning.…”
Section: Discussionmentioning
confidence: 99%